The Economic Value of Serengeti National Park in Tanzania and Implications for Adjacent Local Communities - Kibira, Gerald (School of Economics, 2022)
This study presents a theme on the Economic Value of Serengeti National Park in Tanzania and Implications for Adjacent local communities. Firstly, we introduce and develop a bio-economic model to examine optimal combination of livestock production and wildlife conservation designed for the Serengeti ecosystem in Tanzania. The model incorporates a group of pastoralists who apportion a certain amount of effort between pastoralism and wildlife activities, that is, poaching which kills wildlife. The park agency has a significant role by defining the penalty to the community when its members are caught poaching. The Maasai who live adjacent to Serengeti National Park are found in Loliondo division, which is in Ngorongoro district. This paper articulates a bio-economic model for the two agents, optimizes the market problem for each agent, and relates the outcomes for the park agency and the Maasai community to the social planner's solution. The results show that the market outcomes are suboptimal than the social planner would recommend. Policy implications are that there should be a well-structured community organization that can have a significant impact on the growth of the wildlife stock, through obliging behavior. Such an organization might assist the community to realize a needed social outcome to protect the Serengeti's wildlife. In the second part of the thesis we argue that, National Parks are imperative to protect countries' natural inheritance. They are vital for conservation and offer valuable non-market recreation services to tourists. Benefits from these parks include employment creation, and export incomes. Because of low entrance fees, parks largely depend on fiscal transfers to fund their conservation activities. But dwindling government resources in Africa threaten the existence of national parks and other protected areas. Sustained effective conservation will have to be largely internally funded. Tourism is an important avenue of funds in these circumstances. We measure the nonmarket benefits of Serengeti National Park for international holidaymakers. We make use of data from an on-site survey at the park. We make use of individual Travel cost variables. Models accounting for all problems found in on-site surveys tend to outperform other models. Estimated consumer surplus is large, given the usually low entrance fees. Precise measurement of the travel cost variable is important to arrive at correct welfare estimates. In the third part of this study, we put on a twist in the Contingent Behavior (CB) methodology in the setting of a developing country, which has little application in the literature, which suggests a change in entrance fees at one park and queries how visitation patterns would then change at a substitute park. This allows us to estimate optimal entrance fees for revenue maximization and give an estimation of the demand function. The results indicate there is a possibility of maximizing revenue by raising entrance fee and the demand is elastic. The park agency is not advised to charge the revenue maximizing price because of competition from other parks, both locally and regionally. Nonetheless, the fact that we found that the fees can be raised significantly above the current fees to maximize the revenue collection is important.